Combining escitalopram and cognitive–behavioural therapy for social anxiety disorder: Randomised controlled fMRI trial. (September 2016) - Gingnell, Malin; Frick, Andreas; Engman, Jonas; Alaie, Iman; Björkstrand, Johannes; Faria, Vanda; Carlbring, Per; Andersson, Gerhard; Reis, Margareta; Larsson, Elna-Marie; Wahlstedt, Kurt; Fredrikson, Mats; et al.
Abstract : Background: Selective serotonin reuptake inhibitors (SSRIs) and cognitive–behavioural therapy (CBT) are often used concomitantly to treat social anxiety disorder (SAD), but few studies have examined the effect of this combination. Aims: To evaluate whether adding escitalopram to internet-delivered CBT (ICBT) improves clinical outcome and alters brain reactivity and connectivity in SAD. Method: Double-blind, randomised, placebo-controlled neuroimaging trial of ICBT combined either with escitalopram ( n = 24) or placebo ( n = 24), including a 15-month clinical follow-up (trial registration: ISRCTN24929928). Results: Escitalopram+ICBT, relative to placebo+ICBT, resulted in significantly more clinical responders, larger reductions in anticipatory speech state anxiety at post-treatment and larger reductions in social anxiety symptom severity at 15-month follow-up and at a trend-level ( P = 0.09) at post-treatment. Right amygdala reactivity to emotional faces also decreased more in the escitalopram+ICBT combination relative to placebo+ICBT, and in treatment responders relative to non-responders. Conclusions: Adding escitalopram improves the outcome of ICBT for SAD and decreased amygdala reactivity is important for anxiolytic treatment response.